NEW DISSIMILARITY MEASURES ON PICTURE FUZZY SETS AND APPLICATIONS - Le, Nhung Thi; Nguyen, Dinh Van; Ngoc, Chau Minh; Nguyen, Thao Xuan (Journal of Computer Science and Cybernetics, 2018)
The dissimilarity measures between fuzzy sets/intuitionistic fuzzy sets/picture fuzzy sets are studied and applied in various matters. In this paper, we propose some new dissimilarity measures on picture fuzzy sets. This new dissimilarity measures overcome the restrictions of all existing dissimilarity measures on picture fuzzy sets. After that, we apply these new measures to the pattern recognition problems. Finally, we introduce a multi-criteria decision making (MCDM) method that used the new dissimilarity measures and apply them in the supplier selection problems.